CD24 Expression and B Cell Maturation Shows a Novel Link With Energy Metabolism: Potential Implications for Patients With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - Mensah, Fane F. K.; Armstrong, Christopher W.; Reddy, Venkat; Bansal, Amolak S.; Berkovitz, Saul; Leandro, Maria J.; Cambridge, Geraldine (Frontiers in Immunology, 2018)
CD24 expression on pro-B cells plays a role in B cell selection and development in the bone marrow. We previously detected higher CD24 expression and frequency within IgD+ naïve and memory B cells in patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) compared with age-matched healthy controls (HC). Here, we investigated the relationship between CD24 expression and B cell maturation. In vitro stimulation of isolated B cells in response to conventional agonists were used to follow the dynamics of CD24 positivity during proliferation and differentiation (or maturation). The relationship between CD24 expression to cycles of proliferation and metabolism in purified B cells from HC was also investigated using phospho-flow (phosphorylation of AMPK-pAMPK), 1proton nuclear magnetic resonance and Mitotracker Far-red (Mitochondrial mass-MM). In vitro, in the absence of stimulation, there was an increased percentage of CD24+ viable B cells in ME/CFS patients compared to HC (p< 0.05) following 5 days culture. Following stimulation with B cell agonists, percentage of CD24+B cells in both naïve and memory B cell populations decreased. p< 0.01). There was a negative relationship between percentage of CD24+B cells with MM (R2=0.76; p< 0.01), which was subsequently lost over sequential cycles of proliferation. There was a significant correlation between CD24 expression on B cells and the usage of glucose and secretion of lactate in vitro. Short term ligation of the B cell receptor with anti-IgM antibody significantly reduced the viability of CD24+ memory B cells compared to those cross-linked by anti-IgD or anti-IgG antibody. A clear difference was found between naïve and memory B cells with respect to CD24 expression and pAMPK, most notably a strong positive association in IgD+IgM+ memory B cells. In vitro findings confirmed dysregulation of CD24-expressing B cells from ME/CFS patients previously suggested by immunophenotype studies of B cells from peripheral blood. CD24-negative B cells underwent productive proliferation whereas CD24+ B cells were either unresponsive or susceptible to cell death upon BCR-engagement alone. We suggest that CD24 expression may reflect variations in energy metabolism on different B cell subsets.